92.4k views
2 votes
3(-4n - 9) = 21 plc solve ​

2 Answers

7 votes

Answer:


\Huge \boxed{n=-4}

Step-by-step explanation:

First thing you do is divide by 3 from both sides of equation.


\displaystyle (3(-4n-9))/(3)=(21)/(3)

Simplify.


\displaystyle -4n-9=7

Then add by 9 from both sides of equation.


\displaystyle -4n-9+9=7+9

Simplify.


\displaystyle 7+9=16


\displaystyle -4n=16

Divide by -4 from both sides of equation.


\displaystyle (-4n)/(-4)=(16)/(-4)

Simplify, to find the answer.


\displaystyle 16/-4=-4


\huge\boxed{\textnormal{N=-4}}, which is our answer.

User Corubba
by
5.9k points
2 votes

Answer:


\huge{\boxed{n=-4}}

Step-by-step explanation:


\begin{array}{cc}\begin{flushright}\text{Divide both sides of the equation by 3.}\end{flushright}&\begin{flushleft}-4n-9=7\end{flushleft}\\\begin{flushright}\text{Add 9 on both sides.}\end{flushright}&\begin{flushleft}-4n=16\end{flushleft}\\\begin{flushright}\text{Divide both sides by -4.}\end{flushrigh}&n=-4\end{array}

User Cyberboxster
by
5.1k points